Energi Komunikasi Pembangunan - Wakidul Kohar (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
The effort to build participatory Indonesia has now been replaced by the role of the authorities and businessmen who act more as corrupt, which has been used to inflate the price of development projects, in the name of change, but what is done, is fake changes. In such a situation, action must be immediately initiated rescue. This country requires communicators (leaders, teachers, professors, employees, journalists, students, community leaders, and religious) are able to package a message to arise the spirit of unity and the spirit of life in the new context is strong new social software to hold on social change dynamics sustain through social change, communication development energy.